Evaluation of fatty acid and mineral profiles and bioaccessibility of diosgenin in different types of Peruvian maca (Lepidium meyenii Walp) (Research, Society and Development, 2020)
The present work aimed to study the bioaccessibility of diosgenin, fatty acid and mineral profile in different types of Peruvian maca (Lepidium meyenii Walp). Analyzes of minerals, fatty acids, saponins and bioaccessibility of diosgenin were performed. For minerals the values were detected: commercial litter (MC) 490.65mg / 100g of Ca, 1472.65mg / 100g of K, in red litter (MV) 1478.25mg / 100g of K and 670.25mg / 100g of Ca, yellow yellow (MA) 875.65mg / 100g Ca, 1215.25mg / 100g K. The highest concentrations of fatty acids were related to the unsaturated portion. % oleic acid in the red stretcher. Regarding the saponin and diosgenin content, the commercial litter presented the highest contents 250.33mg / 100g for saponins, and 340.56µg / ml for diosgenin. These results emphasize the importance of the consumption of this nutrient-rich vegetable with effective action on human metabolism (p